Evaluating a training package for health professionals and community workers to spread breast cancer awareness messages. (1st April 2011) - Atkins, L; Forbes, L; Scanlon, K; Jupp, D; Carroll, L; Ramirez, A-J
Abstract : Abstract: Introduction and aims: Delayed presentation in breast cancer leads to more advanced stage at diagnosis and ultimately poorer survival. Delays in presentation are associated with low breast cancer awareness. Breast Cancer Care delivers the Train the Trainer: Breast Health Promotion programme to train people across England to deliver messages to increase breast cancer awareness: knowing how breasts normally look and feel and what breast changes to look for; encouraging regularly looking and feeling for breast changes; early symptomatic presentation and breast screening uptake. We measured trainees' knowledge and confidence to deliver these messages in a before and after observational design. Methods: We recruited 126 trainees attending nine courses over 6 months. Trainees included volunteers, community workers and health professionals. They completed the Cancer Research UK Breast Cancer Awareness Measure at baseline and 1 and 6 months after attending. We also collected information about recipients of the breast cancer awareness messages during the 6 months after training. Results: At baseline, 46% trainees identified five or more non-lump symptoms of breast cancer; 21% identified a 70-year-old woman as at higher risk of breast cancer than a 30 or 50 year old. 50% reported looking and feeling their breasts at least monthly. These proportions are higher than the general population (18%, 14% and 23% respectively).1 Follow-up will finish in March 2011. Conclusion: Breast cancer awareness at baseline was higher than in the general population. We will present 1-month follow-up data at the meeting. The findings will provide the rationale for future investment and improvements in the programme.